Botanical characteristics, matK sequence and preliminary chemical composition of Manuka - Leptospermum scoparium, Myrtaceae - Dien, Nguyen Do Lam; Giang, Nguyen Thi Truc; Lam, Duong Nguyen Xuan (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Leptospermum scoparium is an introduced plant, used as an ornamental in Vietnam. Leptospermum scoparium has anti-inflammatory, antibacterial effects, treats cough, fever, and diarrhea. Objectives: The aim of this study is to investigate the botanical characteristics, matK sequence for identification of Manuka, and preliminary phytochemical screening. Materials and Methods: Fresh trees collected in Bao Loc - Lam Dong; the morphology was evaluated through detailed observation of fresh stem, leaf, and flower specimens. Anatomical studies involved preparing cross-sections with a razor, staining them with carmine and iodine green, and capturing microphotographs using a Samsung digital camera mounted on the microscope. The matK sequence was examined, and the chemical composition of the stem and leaf powder was analyzed using the modified Ciulei method. Results: L. scoparium was identified as Leptospermum scoparium J.R. Forst. & G.Forst., based on morphological characteristics and matK sequence with the following featured morphological characteristics: Simple leaf, alternate, 5 sepals free, 5 petals free, the subpart of the petals is present, numerous stamen arranged in the same circle, 5 carpels, inferior ovary and data of anatomy: Sclereid in endodermis; inner phloem, secretory bags and calci oxalate crystals in the cross-section of the stems and leaves, parenchyma tissue in the cross-section of the leaves have a symmetrical structure; phytochemical constituents of the stems and leaves include: Essential oil, carotenoids, triterpenoids, tannins, reducing agents and organic acids; additionally, the leaves contain anthraquinones, flavonoids, and saponins. Conclusion: The study contributed to providing more data about of morphological characteristics, together with the anatomical characteristics of stems, leaves and the chemical composition of the stems, leaves of Manuka in Vietnam.